Maternity care providers’ experiences of work-related serious events (MATES): An International survey - Maria Healy; Patricia Leahy-Warren; Jean Calleja-Agius; Neville Calleja; Joan Lalor; Eleni Hadjigeorgiou; Marianne Nieuwenhuijze (PLoS ONE, 2025)
Internationally, many women experience physiological childbirth with positive experiences and good health outcomes for them and their baby. For some, due to health complications and context of childbirth they may experience or be perceived as having had a traumatic birth. Ultimately, whether an individual experiences an event as traumatic or not, is a personal experience. Caring for women who experience their birth as traumatic can be challenging. The risk of exposure to a traumatic birth event(s) as part of maternity care providers (MCPs) work, ranges from 67% to 90%. Thereby to support MCPs to provide quality maternal and newborn care, it is important to explore the impact of work-related events. An anonymised online survey relating to MATernity serious EventS (MATES) was developed utilising validated instruments and hosted on QualtricsXM. Following ethical approval, the questionnaire was disseminated internationally across 33 countries between 1st July and 31st December 2022 via social media and the COST Action DEVOTION (CA18211 www.ca18211.eu) network. In total, 579 MCPs responded with a wide age range and years of experience. Descriptive and inferential statistical analyses were performed, including univariate and multivariate linear regression. Data analyses and management were undertaken using SPSS v.20 and two-sided significance tests were applied (α 0.05). The findings suggest that MCPs are exposed to a large variation of serious events and continue to be intensely affected, up to the present day. Events ranged from stillbirth, neonatal death, maternal death, severe or life-threatening maternal or infant incidents and violence and aggression from women or family member. Institutional support for staff is limited, and when available, seldom used. Family and friends were relied on for support, but this does not appear to be associated with MCPs experiencing less secondary traumatic stress. Subsequently MCPs were absence from work through sickness (22%), changed their professional allocation (19%) and seriously considered leaving (42%). Moreover, many reported low to moderate compassion satisfaction and burnout (65–80%). With international scarcity of MCPs, the impact of these events seem to contribute to this shortage. Effective support for MCPs is required if staff are to be recruited and retained.